A Historical Study of Language and Translation in Mashhad’s Theaters: From the Constitutional Revolution to the Islamic Revolution in Iran - Ali Najafzadeh; Saeed Ameri (‫مطالعات زبان و ترجمه, 2024)
Theatrical performances, such as lamentation have always been part of Iranian society and have a long history. However, theater as a cultural and modern phenomenon was introduced to Iranian society in the late Qajar period. In theater, the content of the show, the performance or acting style, and the language used to convey concepts are three crucial elements. Historical studies and translation studies have so far addressed various aspects of theater translation. Nevertheless, the role of language and translation in theater in Mashhad, especially from the Constitutional Revolution to the Islamic Revolution, has been virtually ignored. This paper aims to examine the language and translation as two main elements of theater in Mashhad and analyzes what changes Mashhad’s theater experienced from the first performances in the late Qajar period to the Islamic Revolution. In doing so, drawing on a library method, primary sources, including all Mashhad newspapers from the Constitutional period to the Islamic Revolution, such as Aftab-e-Shargh, Azadi, Bahar, Chaman, Khorasan, Seda-ye Khorasan, Nava-ye Khorasan, etc., were investigated and all the themes related to the theater were extracted. Then, using research and secondary sources, the results related to language and translation were presented in a descriptive-analytical manner. Findings suggest that the early forms of theaters in Mashhad were performed in Turkish. Then Turkish translation was replaced by theaters in Persian. In the first Pahlavi era, the translation of Russian works flourished in Iran, and the translation of prominent Turkish, English, and French works was also added to this trend since 1951. During this period, the quality of translation significantly declined as adaptation or free translation became the norm in play translation. In the 1960s, with the emergence of new theater groups in Mashhad, Persian became the dominant language of this art in Mashhad.